(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2009)
Patients with neck pain both acute and chronic of various aetiologies are commonly found throughout the world for years. Magnetic Resonance Imaging (MRI) is an excellent imaging modality for demonstration of aetiology of neck pain. Degenerative changes, infective processes, neoplastic processes, mechanical injuries and congenital disorders of the spine can be detected by MRI without any hazards. This prospective study of neck pain was done in Radiology and Imaging department of Bangabandhu Sheikh Mujib Medical University and Combined Military Hospital, Dhaka on 60 cases of both sexes reported during the period, February 2006 to September 2006. The aim of the study was to find out the role of MRI in diagnosis and evaluation of chronic and acute neck pain. Out of 60 cases, 51 cases were with cervical spondylotic changes, 2 cases were with spinal trauma, 2 cases were space occupying lesion (SOL) in spinal cord, 1 case was SOL in vertebra, 1 case was soft tissue mass in neck. Only 2 cases showed normal MRI findings. The youngest patient was a fourteen year old male and oldest one was 75 years old male person. Highest incidence was in the 5th decade numbering 20 (33.3%). MRI is non-invasive, non hazardous method and have very few contraindications. Though MRI is relatively expensive and still then it is good considering the diagnostic accuracy and cost effectiveness. Key Words: MRI evaluation, Neck pain. doi: 10.3329/jafmc.v5i1.2849 JAFMC Bangladesh. Vol 5, No 1 (June) 2009 pp.34-36